Studies on the Influence of Moisture and Spedfic Gravity on the Strength Properties of Mango Wood (Mangifera indica) - NAIR, N UNNIKRISHNAN; RAVINDRAN, K; PILLAI, A. G. GOPALAKRISHNA (Fishery Technology, 2017)
Influence of moisture and specific gravity on the strength of mango wood is discussed. The co-efficient of correlation between specific gravity and breaking strength was found to be nonsignificant. The relation of strength and moisture was found to be highly significant. The mean strength values indicated a reduction in strength when the moisture increased from 8.5 to 18.8 %. However no appreciable diff rence in strength values could be observed when moisture increased above 37%. The strength-moisture relationship is a straight line, passing approximately through the fibre saturation point. By using the exponential formula, the breaking strength corresponding to any moisture level between zero and fibre saturation can be determined.